Data from: Shifting balances in the weighting of sensory modalities are predicted by divergence in brain morphology in incipient species of Heliconius butterflies - Dalbosco Dell'Aglio, Denise; McMillan, Owen W.; Montgomery, Stephen (Dryad, 2020)
Integrating and weighting sensory perception across modalities is crucial
to how animals adapt to their environment. Divergence in brain
structure is often in sensory processing regions, suggesting that
investment reflects ecological needs. Here, we use two parapatric closely
related species, Heliconius erato cyrbia and Heliconius himera,
to test the hypothesis that divergence in sensory brain regions
affects foraging decisions. These butterflies are isolated across
an ecological gradient, which is linked to differences in brain
morphology, with H. e. cyrbia investing more in visual centres and H.
himera investing in olfactory centres. Here, we demonstrate that
these two species vary in how they associate visual and olfactory
cues with positive food rewards. We found that when individuals were
trained on paired olfactory and visual stimuli, then presented with these
stimuli in conflict, they showed distinct behavioural responses.
Heliconius himera was more likely to favour positive olfactory cues than
H. e. cyrbia, which favoured visual cues regardless of the paired
stimulus. This suggests that these species have diverged in the
emphasis placed on these different sensory domains during foraging,
consistent with observed differences in brain morphology. This
result strengthens evidence that speciation initiated by
local adaptation is partly facilitated by changes in the neural
basis of key behavioural functions.
This data was collected by scoring observations of butterfly behaviour in
common garden assays. The raw number and proportions of choices are
provided in the full data set file. All statistical analysis are in the R
scripts.
# Data from: Shifting balances in the weighting of sensory modalities are
predicted by divergence in brain morphology in incipient species of
Heliconius butterflies
[https://doi.org/10.5061/dryad.dbrv15f0h](https://doi.org/10.5061/dryad.dbrv15f0h) ## Description of the data and file structure All experiments were recorded using an action camera (GoPro©) during the first 30 min in which flowers were presented. The colour assay was recorded every day, while the odour and conflict assays were recorded on the first, fourth and fifth day due to the reduction of work during the early stages of the Covid-19 pandemic. Using the video footage, the total number of feeding attempts (defined by proboscis extensions) were counted. The data are a cumulative result of all individuals divided in groups (individuals which were tested together). To calculate differences between species, we used linear mixed-effect models (‘glmer’) implemented with the ‘lme4’ package (Bates et al., 2015) using a Poisson distribution, including day and species as fixed factors and group as random factor, followed by analysis of deviance and Tukey's post hoc tests in R (R Core Team, 2020). Student's t test was used to compare the mean against the null hypothesis of random choice (alternative hypothesis is the mean being greater than the presumed probability of 0.33 for colour and 0.5 for odour and conflict). All statistic models are described in the R script below. ### Files and variables Software used: R. #### File: Sensory\_RScript\_DDD.R **Description:** R Script for statistical analysis. This file contains all the packages, statistical models and graphs used in the manuscript. It is divided per analysis in the same order as the published article. To use the script, you need to add the .xlsx tables below. #### File: Sensory\_fulldata2\_DDD.xlsx **Description:** This file contains raw data for statistical analysis. Each tab contains data from a different experiment: ##### Tabs * Tab Pre*_*trial*_*results: This tab contains data from the naive colour choice experiment. Head: "Species" (name of the observed species); "Group" (group of individuals tested together); "Orange" (number of feeding attempts on orange flower); "Red" (number of feeding attempts on red flower); "Pink" (number of feeding attempts on pink flower); "Yellow" (number of feeding attempts on yellow flower); "Total" (total number of feeding attempts); "Orange*_*p" (proportion of feeding attempts on orange flower); "Red_p" (proportion of feeding attempts on red flower); "Pink_p" (proportion of feeding attempts on pink flower); "Yellow_p" (proportion of feeding attempts on yellow flower). * Tab Colour: This tab contains data from the colour choice experiment. Head: "Species" (name of the observed species); "Group" (group of individuals tested together); "Day" (which day of the experiment, from 1 to 5), "Orange" (number of feeding attempts on orange flower); "Red" (number of feeding attempts on red flower); "Pink" (number of feeding attempts on pink flower); "Total" (total number of feeding attempts); "Orange*_*p" (proportion of feeding attempts on orange flower); "Red_p" (proportion of feeding attempts on red flower); "Pink_p" (proportion of feeding attempts on pink flower). * Tab Odour: This tab contains data from the odour choice experiment. Head: "Species" (name of the observed species); "Group" (group of individuals tested together); "Day" (which day of the experiment, using sugar or water), "Orange" (number of feeding attempts on orange scent); "Grass" (number of feeding attempts on lemongrass scent); "Total" (total number of feeding attempts); "Orange*_*p" (proportion of feeding attempts on orange scent); "Grass_p" (proportion of feeding attempts on lemongrass scent). * Tab Conflict: This tab contains data from the conflict experiment. Head: "Species" (name of the observed species); "Group" (group of individuals tested together); "Day" (which day of the experiment: naive, learn or swap), "Orange" (number of feeding attempts on orange flower); "Pink" (number of feeding attempts on pink flower); "Total" (total number of feeding attempts); "Orange*_*p" (proportion of feeding attempts on orange flower); "Pink_p" (proportion of feeding attempts on pink flower).
R Software required to open and run the R scripts.
Keywords: FOS: Biological sciences; butterfly; Behavior; Sensory systems; Visual system; Olfactory system